In-depth considerations for better polyelectrolytes as interfacial materials in polymer solar cells. (March 2016) - Yeo, Jun-Seok; Kang, Minji; Jung, Yen-Sook; Kang, Rira; Lee, Seung-Hoon; Heo, Youn-Jung; Jin, Sung-Ho; Kim, Dong-Yu; Na, Seok-In
Abstract: We perform a comprehensive study to achieve better polyelectrolytes (PEs) as electron-transport layers (ETLs) in polymer solar cells (PSCs). Three well-known PEs – PFN, PEIE, and WPF – are chosen as model systems and investigated with variations in their backbone structures and the state of the amine functionalities on their side chains. Respectively optimized PSCs using the three PEs exhibit different cell-performances, mainly owing to the diode characteristics of built-in potential and recombination strength. To identify how such deviated device-performances correlate with the structural features of PEs, the modulated interfaces of ITO/PEs and PEs/active layer are studied in detail. It is found that conjugated backbones and larger counter-anions on side chains can promote the modulation of ITO work functions (WFs) and that a large amount of protonated amines on PEs is beneficial for junction properties with a subsequent active layer. Additionally, our results indicate that interfacial dipole and electrical doping between the PE and active layer, in addition to WF modulation of the ITO cathode, are important for device efficiency. Accordingly, with the aid of the molecular features of PEIE, PEIE-PSCs exhibit excellent device efficiency and stability compared with PFN- and WPF-PSCs. In the PTB7-th:PC71 BM system, a remarkable power-conversion efficiency of 9.97% is achieved with a single PEIE ETL. Graphical abstract: Highlights: Chemical structure and performance of polyelectrolytes (PEs) in PSCs are correlated. Interfacial dipole and doping between PEs and active layer lead to efficient PSCs. PEIE-based PSCs have excellent device efficiency and high stability. Especially, in the PTB7-th system, encouraging efficiency of 9.97% is achieved.